NCT Dream's Role as A Brand Ambassador Through Buying Interest in the Purchase Decision of Lemonilo Noodles in Bekasi City - Annisa Roudhotul Jannah; Hadita (Dinasti International Journal of Management Science, 2022)
This study aims to find out how big is the role of NCT DREAM as a Brand Ambassador through Buying Interest in the Purchase Decision of Lemonilo Noodles in Bekasi City. The method used in this study is a quantitative method, which in this study uses accidental sampling technique in determining the sampling method. The basis of the study used 186 respondents to be used as samples in the study, which in this study used primary data obtained by distributing questionnaires to consumers of Lemonilo noodles in Bekasi City. The results show that 1) Brand Ambassador has a significant effect on Buying Interest, 2) Brand Ambassador has no significant effect on Purchase Decisions, 3) Buying Interest has a significant effect on Purchase Decisions, 4) Buying Interest significantly mediates Brand Ambassador's decision. Purchase.